Pliocene-Pleistocene evolution of sea surface and intermediate water temperatures from the Southwest Pacific - McClymont, Erin L.; Elmore, Aurora C.; Kender, Sev; Leng, Melanie J.; Greaves, Mervyn; Elderfield, Henry (Wiley-Blackwell, 2016)
Over the last 5 million years, the global climate system has evolved toward a colder mean state, marked by large amplitude oscillations in continental ice volume. Equatorward expansion of polar waters and strengthening temperature gradients have been detected. However, the response of the mid- and high-latitudes of the southern hemisphere is not well documented, despite the potential importance for climate feedbacks including sea ice distribution and low-high latitude heat transport. Here, we reconstruct the Pliocene-Pleistocene history of both sea surface and Antarctic Intermediate Water (AAIW) temperatures on orbital timescales from DSDP Site 593 in the Tasman Sea, Southwest Pacific. We confirm overall Pliocene-Pleistocene cooling trends in both the surfaceocean and AAIW, although the patterns are complex. The Pliocene is warmer than modern, but our data suggest an equatorward displacement of the subtropical front relative to present, and a poleward displacement of the subantarctic front of the Antarctic Circumpolar Current (ACC). Two main intervals of cooling, from c.3 Ma and c.1.5 Ma, are coeval with cooling and ice sheet expansion noted elsewhere, and suggest that equatorward expansion of polar water masses also characterised the Southwest Pacific through the Pliocene-Pleistocene. However, the observed trends in SST and AAIW temperature are not identical despite an underlying link to the ACC, and intervals of unusual surface ocean warmth (c.2 Ma) and large amplitude variability in AAIW temperatures (from c.1 Ma) highlight complex interactions between equatorward displacements of fronts associated with the ACC and/or varying poleward heat transport from the subtropics.